Tugas Bahasa Inggris berbasis Personal dan Disiplin: Keterlibatan dan Kinerja Praja dan Taruna - Nurlaeli Hidayanti; Meyke Jayanti Kinasih; St. Hariati Buchori (Jurnal Intelek Insan Cendikia, 2026)
This study compares cadets’ observable behavioral engagement and English performance in personally relevant and discipline-based video tasks. It adopts a paired comparative design within a convergent mixed-methods framework. The data sources comprise two task products from the same 62 cadets—21 from Applied Indonesian Politics, 21 from Public Policy Studies, and 20 from Economic Development and Community Empowerment—yielding 124 videos, their transcripts, and submission metadata. Quantitative evidence includes analytic-rubric scores, punctuality of submission, video duration, word count, and other behavioral indicators, while qualitative content analysis examines elaboration, concrete experience, multimodal creativity, expressiveness, and script dependence. In the simulated dataset, personal tasks produced higher engagement (M = 4.03, SD = 0.44) than discipline-based tasks (M = 3.47, SD = 0.57), t(61) = 6.88, p < .001, d = 0.87. Overall English performance was also higher in personal tasks, although the effect was small (d = 0.30). By contrast, discipline-based tasks generated stronger technical vocabulary, academic register, and conceptual accuracy but were accompanied by substantially greater script dependence. The findings suggest that personal and disciplinary relevance support different dimensions of task performance rather than representing mutually exclusive instructional choices. The study proposes a Personal–Disciplinary Bridge model that uses cadets’ local experiences as an entry point for analyzing politics, public policy, governance, economic development, and community empowerment.